Currency hedging strategy using barrier options in the colombian market - Mariana Arango-Franco; Miguel Jiménez-Gómez; Natalia Acevedo-Prins (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
One of the main problems for the growth of the Colombian market is the short variety of investment instruments found in the local market. In this way, an exchange rate hedging strategy is proposed using exotic options, specifically, barrier-type options. These types of options are not offered in the Colombian market. Monte Carlo simulation is used to determine the effect that the hedging strategy has on currency risk. From the results, it is concluded that the exchange risk is decreased with the hedging strategy because the 5th and 95th percentiles are lower than in the scenario without hedging. Finally, the code that was used to model the barrier options is explained.